Correlation of Chest Circumference and Body Length Towards Body Weight, Carcas and Non-Carcas Weight of Bali Beef Slaughtered at Kefamenanu City Slaughterhouse - Sebastianus, Antonius; Oktovianus Rafael Nahak; Aristo Kurniawan Sio (Jurnal Peternakan Nusantara, 2025)
Balinese cattle are one of the local cattle breeds that have great potential in supporting domestic meat needs. As beef cattle, Balinese cattle are known to have high adaptability to Indonesia’s tropical environment and good fertility rates, making them the right choice to be developed in order to increase the availability of animal food. This study aims to determine the correlation value of chest circumference and body length to body weight, carcass and non-carcass weight of 56 Balinese cattle slaughtered at the Slaughterhouse in Kefamenanu City. Data analysis uses descriptive analysis to determine body weight, chest circumference, carcass weight, and non-carcass weight. The results of the study showed that in the Kefamenanu RPH, the average body length was 122.71 cm, producing a body weight of 212.02 kg, a carcass weight of 67.34 kg and a carcass weight of 145.54. While the average chest circumference of Balinese cattle that were slaughtered with non-weight was 167.59 cm, producing a body weight of 212.02 kg, a carcass weight of 67.34 kg and a non-carcass weight of 145.54 kg, the correlation value between body length and body weight, carcass weight and non-carcass weight of Balinese cattle ranged from 0.071-0.46, and the correlation value between chest circumference and body weight, carcass weight and non-carcass weight of Balinese cattle ranged from 0.223-0.444. Based on this study, the carcass and non-carcass weight produced, the Kefamenanu RPH needs to set a standard for the body weight of Balinese cattle that are slaughtered